Analysis of raft foundation with geofoam for earthquake resistant - Mohd Taftazani Bin Ahmad (School of Environmental Engineering, University Malaysia Perlis, 2014)
It is becoming a great challenge for civil engineers to design a foundation with able to restrain form an earthquake. The paper presents the settlements of raft foundation (static load) and the effects of raft foundation (include building on it) that expose to an earthquake. In this process, geofoam, Expanded Polystyrene (EPS) is placed under foundation. The properties of this type of geofoam is super-lightweight closed cell, rigid, plastic foam. High strength give best option as fill for poor quality of soil.